Panoramic Behavior of Renyi Holographic Dark Energy in f(R,T) Gravity (Journal of Scientific Research, 2026)
The main motive of this study is to investigate behaviors of Renyi holographic dark energy (RHDE) for anisotropic and homogenous space-time in the framework of f(R,T) gravity. The field equations are solved using (i) the shear scalar of the metric is proportional to the expansion scalar which results a relationship between metric potentials and (ii) special law of variation of Hubble's parameter (Berman (1983)) that yields constant deceleration parameter. The cosmological parameters like energy density, EoS parameter, statefinder parameters, jerk parameter of the model are obtained and discussed their physical significance in the light of the recent scenario of accelerated expansion of the universe and cosmological observations.